2015
DOI: 10.1089/vbz.2014.1619
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Zoonotic Helminthiases of Murid Rodents from the Indo-Chinese Peninsula: Impact of Habitat and the Risk of Human Infection

Abstract: In this study, we report the potential rodent-borne zoonotic helminths in wild-caught murid rodents from four categorized habitats-forest, nonflooded land, irrigated land, and human settlement in seven localities of Thailand, Cambodia, and Lao PDR. Out of 2478 rodent samples, 735 (29.7%) were infected by at least one of the following zoonotic helminth species: Echinostoma malayanum, Echinostoma ilocanum, Plagiorchis muris, Raillietina spp., Hymenolepis diminuta, Hymenolepis nana, Cyclodontostomum purivisi, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 63 publications
0
38
0
2
Order By: Relevance
“…Although the high prevalence of C. hepatica in commensal rodents may increase the health risk in humans, to date human seroprevalence has not been examined in SEA. Our study detected all the rodent-borne zoonotic nematodes and cestodes reported by Chaisiri et al (2015) except Cyclodontostomum purvisi. Thus, there can be no doubt that in the studied wet markets there is a potentially high risk of rodent-borne transmission.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…Although the high prevalence of C. hepatica in commensal rodents may increase the health risk in humans, to date human seroprevalence has not been examined in SEA. Our study detected all the rodent-borne zoonotic nematodes and cestodes reported by Chaisiri et al (2015) except Cyclodontostomum purvisi. Thus, there can be no doubt that in the studied wet markets there is a potentially high risk of rodent-borne transmission.…”
Section: Discussionmentioning
confidence: 52%
“…The aforementioned studies of SEA markets (Claveria et al, 2005) (Paramasvaran et al, 2009;Tung et al, 2013), as well as in urban habitats (Mohd Zain et al, 2012), report the presence of the same zoonotic helminths as recovered in the present study (see details in Table 1). According to the review by Chaisiri et al (2015), four of our recovered helminths (H. diminuta, H. nana, Raillietina sp. and M. monoliformis) are potentially zoonotic species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations